2015
DOI: 10.1039/c5dt01854d
|View full text |Cite
|
Sign up to set email alerts
|

An anion induced multisignaling probe for Hg2+and its application for fish kidney and liver tissue imaging studies

Abstract: 3',6'-Bis(diethylamino)-2-(pyridin-2-ylmethyl)spiro[isoindoline-1,9'-xanthen]-3-one () was synthesized for the selective fluorescence and colorimetric recognition of Hg(2+) at pH 6.0. In addition, was useful for imaging Hg(2+) in fish kidney and liver tissues using a fluorescence microscope. Spirolactam ring opening of for Hg(2+) recognition is strongly influenced by the nature of the mercury salt and found to be NO3(-)-induced. Other mercury salts such as HgCl2, Hg(CH3COO)2 and Hg(ClO4)2 failed to induce fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Some xanthone derivatives, which are developed as fluorescent metal probes, were previously reported to form colored complexes with several metals [18][19][20][21][22]. We also reported that the series of xanthones reported herein behaved as potent cytotoxic drugs against cervical, colorectal, hepatocellular and alveolar adenocarcinoma cell lines, with IC 50 values mostly in units or tens of µM concentrations [23].…”
Section: Introductionmentioning
confidence: 53%
“…Some xanthone derivatives, which are developed as fluorescent metal probes, were previously reported to form colored complexes with several metals [18][19][20][21][22]. We also reported that the series of xanthones reported herein behaved as potent cytotoxic drugs against cervical, colorectal, hepatocellular and alveolar adenocarcinoma cell lines, with IC 50 values mostly in units or tens of µM concentrations [23].…”
Section: Introductionmentioning
confidence: 53%
“…In this example the chloridomercury array forms a more ordered grid around the copper cations, likely due to additional coordination of one nitrogen atom from the copper bound ligand to mercury. In addition, another interesting compound has a repeating [Hg 3 Cl 9 (H 3 L)] ⋅ 2H 2 O unit, where H 3 L=tri‐cationic N , N , N ′, N ′‐tetraethyl‐3‐oxo‐2‐(1‐pyridin‐2‐ylmethyl)‐2,3‐dihydrospiro[isoindole‐1,9′‐xanthene]‐3′,6′‐diammonium [47] . In this latter example, all Hg−Cl bonds are within the sum of the ionic radii (range: 2.334(3)–2.739(2) Å), and the chain is connected by four elongated Hg−Cl interactions (3.086(2)–3.3477(19) Å), with a degree of Cl … H interaction with the lattice water molecule.…”
Section: Structural Discussionmentioning
confidence: 99%
“…Two compounds, 9-[1-(2-methyl-4-methoxyphenyl)]-6-hydroxy-3H-xanthen-3one (Tokyo green) and another fluorescein derivate 9-[1-(4tert-butyl-2-methoxyphenyl)]-6-hydroxy-3H-xanthen-3-one (Granada green) are sensitive dyes for intracellular phosphate detection [8,9], 3',6'-bis(4-guanidinobenzoyloxy)-5-(N'-4-carboxylphenyl)thioureidospiro[isobenzofuran-1(3H), 9'- [9H]xanthen]-3-one is useful for the detection of plasminogen activator activity [10] and 3',6'-bis(diethylamino)-2-(pyridine-2-ylmethyl)spiro[isoindoline-1,9'-xanthen]-3-one is highly efficient for the recognition and determination of Hg 2+ . [11] Research has also been targeted to xanthene-9ones. Two of these compounds showed anticancer properties.…”
Section: Synthesis Of Xanthene-3-ones (9-aryl-6-hydroxy-3h-mentioning
confidence: 99%